Short Communication: The nest characteristics of Wreathed Hornbill (Rhyticeros undulatus) in Mount Ungaran, Central Java, Indonesia - MARGARETA RAHAYUNINGSIH; NUGROHO EDI KARTIJONO; AMIN RETNONINGSIH (Society for Indonesian Biodiversity, 2017)
Rahayuningsih M, Kartijono NE, Retnoningsih A. 2017. Short Communication: The nest characteristics of Wreathed Hornbill (Rhyticeros undulatus) in Mount Ungaran, Central Java, Indonesia. Biodiversitas 18: 1130-1134. Java has three species of hornbills, one of them is the Wreathed Hornbill (Rhyticeros undulates Shaw, 1811) that can be found mainly throughout on Mount Ungaran, Central Java, Indonesia. The main threats to Wreathed Hornbill population are habitat fragmentation and forest clearing. The large trees used for nesting by the Wreathed Hornbill are usually located in areas of illegal logging. Therefore, it is necessary to study the characteristics of Wreathed Hornbill nests, especially in Mount Ungaran. Eight nests were discovered, six of which were active. The nests were found at 900-1200 m above sea level. Trees that were used as nest sites were between 24-35 m high, and had a diameter of 0.83-1.75 m. Nests were located at heights of 1-27 m, and had a hole diameter of 33-38 cm, hole length of 170-211 cm, entrance width of 4-11 cm, entrance length of 14-39 cm, nest thickness 6-18 cm, and a temperature of 20-21Â°C. The nest shapes were oval, ellipse, and irregular oval. Commonly, the Wreathed Hornbills used Syzygium glabratum, Syzygium antisepticum, and Cratoxylum formosum for nesting.